IbM KELOMPOK USAHA CAMILAN â€œSUMBER REJEKIâ€ - Suparno Suparno; Dantje Salean; Hendro Tjahjono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2015)
â€œSumber Rejekiâ€ micro owner is Mr.Suwito and Mr. Adi Suprianto which located at Desa Cangkring Kecamatan Ngadirojo Kabupaten Pacitan. This business has been established in 2007 and operated in the field of business Kolong Klitik. The main problems faced through â€œSumber Rejekiâ€ micro business are the quantity of production is not optimal yet and both couldâ€™nt make financial bookkeeping business and less distribution. By using science and technology from the Ipteks bagi Masyarakat (IbM) can be expected improving the quantity and quality of Kolong Klitik production, as well as to make financial efforts and to expand marketing network.Keywords : Production, Finance and Marketing.